An Alternative Technique of Bleaching Vital Tooth: A Case Report - Lora Mishra1, Pratima Panda2, Shashirekha Govind3, Debkant Jena1, Manoj Kumar4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fluorosis staining is commonly considered an esthetic problem because of the psychological impact ofunesthetic maxillary anterior teeth. Numerous treatment approaches have been proposed, ranging frombleaching to enamel reduction to restorative techniques. The aim of this study was to report the clinical caseof a female patient of 18 years with moderate fluorosis with midline diastema, whose smile was reestablishedby the application of 5%sodium hypochlorite bleaching agent after cleaning and enamel etching with 37%phosphoric acid followed by direct composite veneering. This technique showed excellent results and thepatient was satisfied. This technique is simple,low cost,painless, fast and easy to perform, in addition topreserving the dental structure. Treatment showed immediate and permanent results.